The impact of policy uncertainty on stock liquidity in Vietnam’s M&A market - Dang Huu Man; Nguyen Manh Toan (Tạp chí Khoa học và Công nghệ, 2023)
This study investigates the impact of policy uncertainty on stock liquidity in Vietnam’s M&A market. Using a comprehensive sample of M&A acquisition deals over the 2005-2020 period, we find that policy uncertainty is negatively associated with stock liquidity of target firms, indicating that firms should increase their information disclosure to improve the information environment during periods of increased asymmetric information due to policy uncertainty. We also find that higher levels of policy uncertainty lead to lower market valuations of target firms, reflecting greater market skepticism about the completion of the transaction and related synergy benefits. This study highlights the importance of transparency in improving stock liquidity and suggests that policymakers need to consider the impact of domestic economic and investment policies on M&A activity and stock liquidity in Vietnam.